A National Equity Initiative to Address Noncommunicable Diseases and Injuries: Findings and Recommendation from the Nepal NCDI Poverty Commission - Koirala, B.; Adhikari, S. R.; Shrestha, A.; Vaidya, A.; Aryal, K. K.; Kalaunee, S. P.; Shrestha, A.; Mishra, S. R.; Sharma, S. K.; Karki, A.; Maharjan, B.; Singh, S.; et al. (Kathmandu University Medical Journal, 2022)
We aimed to assess the burden of NCDIs across socioeconomic groups, their economic impact, existing health service readiness and availability, current policy frameworks and national investment, and planned programmatic initiatives in Nepal through a comprehensive literature review. Secondary data from Global Burden of Disease estimates from GBD 2015 and National Living Standard Survey 2011 were used to estimate the burden of NCDI and present the relationship of NCDI burden with socioeconomic status.The Commission used these data to define priority NCDI conditions and recommend potential cost-effective, poverty-averting, and equity-promoting health system interventions. NCDIs disproportionately affect the health and well-being of poorer populations in Nepal and cause significant impoverishment.The Commission found a high diversity of NCDIs in Nepal, with approximately 60% of the morbidity and mortality caused by NCDIs without primary quantified behavioral or metabolic risk factors, and nearly half of all NCDI-related DALYs occurring in Nepalese younger than 40 years. The Commission prioritized an expanded set of twenty-five NCDI conditions and recommended introduction or scale-up of twenty-three evidence-based health sector interventions. Implementation of these interventions would avert an estimated 9680 premature deaths per annum by 2030 and would cost approximately $8.76 per capita. The Commission modelled potential financing mechanisms, including increased excise taxation on tobacco, alcohol, and sugar-sweetened beverages, which would provide significant revenue for NCDI-related expenditures. Overall, the Commission’s conclusions are expected to be a valuable contribution to equitable NCDI planning in Nepal and similar resource-constrained settings globally.